Factors that Affect Prognosis and Morbidity in Pediatric Patients with Carbon Monoxide Poisoning - Yılmaz Seçilmiş; Mehmet Adnan Öztürk (Galenos Yayinevi, 2018)
Introduction:Carbonmonoxide poisoning continues to be a major health problem worldwide, especially in developing countries, and constitutes an important part of the patients admitted to the pediatric emergency clinics due to poisoning. The aim of this study was to evaluate the correlation between clinical severity, morbidity, hospital stay, intensive care need, and full systemic effects in patients who were followed up and treated for carbon monoxide poisoning in our pediatric emergency clinic.Methods:The study was performed between January 2013 and 2015. We included patients under 18 years of age who were admitted to the pediatric emergency with carbon monoxide poisoning. Assessments were made prospectively. The epidemiological characteristics, complaints, physical examination and vital findings of all patients were recorded. Carboxyhemoglobin (COHb) level, oxygen saturation, electrocardiography, complete blood count, liver and kidney functions, and cardiac enzymes were studied, and Glasgow Coma scale (GCS) was calculated.Results:The mean length of hospital stay for 232 patients was calculated as 7.08±1 hours and the mean duration of exposure to carbon monoxide gas was 3.17±2.5 hours. Higher COHb levels and cardiotoxicity were detected in patients with a longer duration of exposure and a lower GCS and an increased intensive care need (p<0.01). There was no correlation between COHb levels and clinical severity, GCS, or intensive care unit need. However, it was found that high COHb levels (especially above 30%) increased cardiac injury and neurological symptoms but did not cause a permanent sequela (p<0.05). None of the patients had permanent neurological, cardiac, or renal damage.Conclusion:We found that duration of exposure is the most important and accurate parameter for the evaluation of clinical course and morbidity. In patients with high COHb levels, the effects are more prominent, however, we considered that there was no change in sequelae at long-term follow up.